2013
DOI: 10.1063/1.4818580
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of dark Si nanocrystals in SiO2 and their role in external quantum efficiency quenching

Abstract: The percentage of dark silicon nanocrystals, i.e., the nanocrystals that are not able to radiatively recombine after absorption of a photon, is investigated by combining measurements of external and internal quantum efficiencies. The study is conducted on samples prepared by co-sputtering and subsequent heat treatments. We show that the external quantum efficiency is mainly limited by the presence of dark nanocrystals, which induce losses after direct excitation and also, as we propose, by indirect excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
3
34
2
Order By: Relevance
“…22,37,43 In contrast, here we report IQE = 100% for Si NCs passivated with different ligand molecules in a full emission energy range, in which the nonradiative recombination channels of this type seem to be totally suppressed. A partial coverage of nanocrystal surface by oxygen molecules was confirmed here by FTIR measurements ( Figure S2); hence a thick oxide shell is probably required to facilitate such a transition.…”
Section: Articlecontrasting
confidence: 62%
“…22,37,43 In contrast, here we report IQE = 100% for Si NCs passivated with different ligand molecules in a full emission energy range, in which the nonradiative recombination channels of this type seem to be totally suppressed. A partial coverage of nanocrystal surface by oxygen molecules was confirmed here by FTIR measurements ( Figure S2); hence a thick oxide shell is probably required to facilitate such a transition.…”
Section: Articlecontrasting
confidence: 62%
“…Obviously, longer dark intervals will result in lower values of PL QY. Ultimately, some NCs can occur to have infinite dark intervals and in literature they are called “dark” NCs . Such “dark” NCs together with blinking NCs in their OFF‐state behave like “black holes”, i.e., they absorb photons, but do not contribute to the emission and so lower the PL QY.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the EQY in range #1 indirectly reflects the level of the "optical activity" of Si NCs. 40 In the investigated material, the optical activity of Si NC is quite low and can be improved. Past investigations have shown that in carefully optimized materials the optical activity of Si NCs can reach 60%.…”
Section: Application Potentialmentioning
confidence: 99%
“…To this end, the low temperature post-annealing in H 2 environment could be explored, since it has been shown to enhance the optical activity within ensembles of Si NCs, reducing the number of the so-called "dark" NCs undergoing fast nonradiative quenching of excitons. 40 For improvement of EQY in regions #2-4, the hot-carrier mediated excitation must be optimized. Here, the current study provides clear guidance, suggesting that the highest efficiency can be expected for materials with moderate concentrations of relatively small NCs of superior crystalline quality, and a high Er-to-NC concentration ratio.…”
Section: Application Potentialmentioning
confidence: 99%